The Development of a comprehensive evaluation system for residents in general surgery residency training programs - Crisostomo, Armando C. (1997)
This project describes the development of a standard evaluation system that started in 1992 when the Philippine College of Surgeons (PCS) mandated the author to chair an ad hoc committee for that specific purpose. A standard evaluation system seeks to complement the standard curriculum for general surgery training, ensure uniform evaluation standards and hopefully, lead to improvement in the quality of postgraduate training in surgery. The methodology consisted of the following: 1) Conducting a consensus workshop among experts to determine the most important competencies, general evaluation criteria and most appropriate evaluation instruments (September 12, 1992); 2) Development of the evaluation instruments (October 1992-March 1993); 3) Deliberation and revision of instruments by the PCS Committee in Surgical Training (March 1993-June 1993); 4) Pilot testing of the evaluation instruments (July-December 1993); 5) Revision based on feedback from pilot testing; 6) Deliberations and approval by the PCS Board of Regents; 7) Conduct of trainer workshop (April and May 1994); 8) Full implementation of evaluation system in all PCS accredited residency training program (starting January 1995). The major criteria for evaluation and the evaluation instruments include: 1) Basic theoretical knowledge, through objective written examinations and oral examinations; 2&3) Clinical competence and Technical Skills through observational rating scales; 4) Attitudinal competencies. Implementation of the evaluation system needs to be continuously re-assessed and feedback obtained from both faculty and surgical trainees so that the system may be revised, further improved and hopefully, lead to the ultimate goal of improving the quality of surgical care being given to our people.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Surgery -- Study and teaching (Residency)